Chinese residents' educational disparity and social insurance coverage. Issue 7 (13th August 2018) - Lee, Yen-Han; Chiang, Timothy; Shelley, Mack; Liu, Ching-Ti
Abstract : Purpose: The Chinese society has embraced rapid social reforms since the late twentieth century, including educational and healthcare systems. The Chinese Central Government launched an ambitious health reform program in 2009 to improve service quality and provide affordable health services, regardless of individual socio-economic status. Currently, the Chinese social health insurance includes Urban Employee Basic Medical Insurance, Urban Resident Basic Medical Insurance, and New Cooperative Medical Insurance for rural residents. The purpose of this paper is to measure the association between individual education level and China's social health insurance scheme following the reform. Design/methodology/approach: Using the latest (2011) China Health and Nutrition Survey (CHNS) data and multivariable logistic regression models with cross-sectional design ( n =11, 960), the odds ratios (OR) and 95% confidence intervals (95% CI) are reported. Findings: The authors found that education is associated with all social health insurance schemes in China after the reform ( p <0.001). Residents with higher educational attainments, such as technical school (OR: 6.64, 95% CI: 5.44–8.13) or university and above (OR: 9.86, 95% CI: 8.14–11.96), are associated with UEBMI, compared with lower-educated individuals. Practical implications: The Chinese Central Government announced a plan to combine all social health insurance schemes by 2020, except UEBMI, a plan with the most comprehensive financial package. Further research is needed to investigate potential disparities after unification. Policy makers should continue to evaluate China's universal health coverage and social disparity. Originality/value: This study is the first to investigate the association between residents' educational attainment and three social health insurance schemes following the 2009 health reform. The authors suggest that educational attainment is still associated with each social health insurance coverage after the ambitious health reform.